Integrating Social Media Platforms into Effective Language Teaching Practices - Robinson X,; Dr. P.N. Gunanidhi, Ph.D, (International Journal of Scientific Research in Science and Technology, 2024)
Social media has transformed communication and interaction, becoming a key element in modern education, particularly in language learning. This research examines the intersection between social media and language pedagogy, focusing on the integration of platforms like Facebook, Twitter, Instagram, and TikTok into language teaching. The study explores how these platforms offer improved communication, resource accessibility, and community building for learners, while also highlighting challenges such as information overload, distraction, and privacy concerns. The implications for educators in terms of professional development, curriculum design, and assessment adaptations are also discussed. The findings suggest that while social media offers valuable opportunities for language learning, its successful integration requires structured approaches to mitigate potential drawbacks.
Keywords: Social Media Integration; Language Learning; Language Pedagogy; Collaborative Learning; Distraction in Education; Resource Accessibility